The Relationship of Attachment Style and Emotional Intelligence: The Moderating Role of Gender - Rebernjak, Blaž; Marjanović, Iva; Buško, Vesna (2008)
The association of attachment style and emotional intelligence (EI) with a possible moderating effect of gender was investigated in a sample of 281 Croatian students. Previous studies indicated the existence of connection between parental warmth and emotional intelligence, and between attachment and emotional intelligence, although this relationship was not thoroughly explored. Moderated hierarchical regression analysis indicated weak to moderate relationship between attachment style and two ability measures of EI. Male participants who exhibit negative model of self (anxious and fearful attachment styles) scored lower on EI measures than those exhibiting positive model of self (secure and dismissive attachment styles). Female participants, on the other hand, scored more or less consistently on EI (depending on the measure used) no matter what their attachment style was.
Projekt MZOS
ENG